2008
DOI: 10.1016/j.jtcvs.2008.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Is lung cancer resection indicated in patients with idiopathic pulmonary fibrosis?

Abstract: Although idiopathic pulmonary fibrosis causes high mortality after pulmonary resection for lung cancer and poor long-term survival, long-term survival is possible in patients with these two fatal diseases. Therefore, in selected patients, idiopathic pulmonary fibrosis may not be a contraindication to pulmonary resection for stage I lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
126
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(134 citation statements)
references
References 25 publications
7
126
0
1
Order By: Relevance
“…The surgical option is also associated with poor outcomes for this patient population. The American College of Chest Physicians and Society of Thoracic Surgeons consensus recently identified patients with IPF as high-risk patients with increased risk of complications following surgical resection with overall reduced survival and increased risk of mortality and pulmonary complication (34)(35)(36).…”
Section: Toxicities and Pulmonary Fibrosismentioning
confidence: 99%
“…The surgical option is also associated with poor outcomes for this patient population. The American College of Chest Physicians and Society of Thoracic Surgeons consensus recently identified patients with IPF as high-risk patients with increased risk of complications following surgical resection with overall reduced survival and increased risk of mortality and pulmonary complication (34)(35)(36).…”
Section: Toxicities and Pulmonary Fibrosismentioning
confidence: 99%
“…Unsurprisingly, patients with IPF who undergo resection for lung cancer have significantly higher rates of post-operative mortality and morbidity, as well as worse long-term outcomes, than patients without IPF who undergo pulmonary resection. Hospital mortality rates for IPF patients range from 7.1% to 18.2% with post-operative acute exacerbations of IPF the major cause of death [42][43][44][45]. Rates of post-operative exacerbations of IPF are related to the extent of resection, with significantly higher rates in patients undergoing pneumonectomy than lobectomy and no significant difference in post-operative mortality and morbidity in patients with pulmonary fibrosis undergoing limited resections (segmentectomy or wedge resection) compared with the general lung cancer population [42,43].…”
Section: Prognosis and Treatmentmentioning
confidence: 99%
“…Hospital mortality rates for IPF patients range from 7.1% to 18.2% with post-operative acute exacerbations of IPF the major cause of death [42][43][44][45]. Rates of post-operative exacerbations of IPF are related to the extent of resection, with significantly higher rates in patients undergoing pneumonectomy than lobectomy and no significant difference in post-operative mortality and morbidity in patients with pulmonary fibrosis undergoing limited resections (segmentectomy or wedge resection) compared with the general lung cancer population [42,43]. Some studies have suggested that pre-operative pulmonary function tests may predict increased risk of postoperative exacerbations [42,45], but other studies have not found a link between pre-operative pulmonary status and post-operative acute exacerbations [43].…”
Section: Prognosis and Treatmentmentioning
confidence: 99%
See 2 more Smart Citations